The ex-husband - Hamilton, Karen (Karen J.) (Graydon House, 2022)
Taking a personal assistant position for an extravagant-and mysterious-engagement party on board a superyacht, former con artist Charlotte becomes trapped with someone who knows her past and is hell-bent on making her pay for it.